Diagnosing Asthma Expert System with Case Base Reasoning Methods - Kune, Margaritha M.; Panggabean, Erwin (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Asthma is a disease that is Often found in society, especially in the elderly. Asthma is a long-term chronic disease, if left to be fatal and can cause death. Limited access and costs, to patient health information, it is difficult, to know how much influence the disease. So to find out it needs to be built a simple application that can help and Facilitate the community. The purpose of this application is to identify asama disease in older people with 15 symptoms. For the development of expert systems, Several stages are needed items, namely: Analysis and Design of the data collection. This expert system application complies with asthma used by experts and users.